2022
DOI: 10.3390/molecules27030625
|View full text |Cite
|
Sign up to set email alerts
|

Use of Onion Waste as Fuel for the Generation of Bioelectricity

Abstract: The enormous environmental problems that arise from organic waste have increased due to the significant population increase worldwide. Microbial fuel cells provide a novel solution for the use of waste as fuel for electricity generation. In this investigation, onion waste was used, and managed to generate maximum peaks of 4.459 ± 0.0608 mA and 0.991 ± 0.02 V of current and voltage, respectively. The conductivity values increased rapidly to 179,987 ± 2859 mS/cm, while the optimal pH in which the most significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 67 publications
0
12
0
1
Order By: Relevance
“…2.5 Caracterización de las celdas de combustible microbiana. La caracterización diaria de corriente y voltaje se realizaron mediante un multímetro, marca Prasek Premium PR-85, y una resistencia externa de 100 Ω. Por otro lado, los valores de densidad de corriente (DC) y densidad de potencia (DP) fueron realizados mediante resistencia externas 10 ± 0.2, 40 ± 2.3, 50 ± 2.7, 100 ± 3.2, 300 ± 6.2, 390 ± 7.2, 560 ± 10, 680 ± 12.3, 820 ± 14.5, 1000 ± 20.5 Ω; mediante la fórmula DC=I/A y DP=IV/A [23], donde I es la corriente con diferentes resistencias externas, V es el voltaje de las celdas a circuito abierto y A el área (144 ± 5.2 cm 2 ). El monitoreo de los cambios de la conductividad (conductivity meter CD-4301) y el pH (pH-meter 110 Series Oakton) también fueron medidas.…”
Section: Identificación M Olecular De Galactomyces Spunclassified
“…2.5 Caracterización de las celdas de combustible microbiana. La caracterización diaria de corriente y voltaje se realizaron mediante un multímetro, marca Prasek Premium PR-85, y una resistencia externa de 100 Ω. Por otro lado, los valores de densidad de corriente (DC) y densidad de potencia (DP) fueron realizados mediante resistencia externas 10 ± 0.2, 40 ± 2.3, 50 ± 2.7, 100 ± 3.2, 300 ± 6.2, 390 ± 7.2, 560 ± 10, 680 ± 12.3, 820 ± 14.5, 1000 ± 20.5 Ω; mediante la fórmula DC=I/A y DP=IV/A [23], donde I es la corriente con diferentes resistencias externas, V es el voltaje de las celdas a circuito abierto y A el área (144 ± 5.2 cm 2 ). El monitoreo de los cambios de la conductividad (conductivity meter CD-4301) y el pH (pH-meter 110 Series Oakton) también fueron medidas.…”
Section: Identificación M Olecular De Galactomyces Spunclassified
“…Likewise, in MFCs, oxidation and reduction processes take place while COD is eliminated and electricity is generated [32].…”
Section: B Construction Of the Microbial Fuel Cellsmentioning
confidence: 99%
“…Rojas et al (2022) demonstrated electricity generation from onion residues, generating maximum peaks of 4.459 ± 0.0608 mA and 0.991 ± 0.02 V of current and voltage, respectively. The species they identified at the molecular level were Pseudomona aeruginosa, Acinetobacter bereziniae, Stenotrophomonas maltophilia, and Yarrowia lipolytica adhered to the anode electrode [21]. Meanwhile, Bose et al (2019) identified six species of exoelectrogenic bacteria that degrade organic matter in wastewater.…”
Section: Introductionmentioning
confidence: 99%